Protection of Farmers Copyright Rights in A Cleaning Agreement By Regional Government - Deasy Soeikromo; Mercy M M Setlight; Sarah D L Roeroe; Maya Kurendang (LPPM Universitas PGRI Sumatera Barat, 2023)
North Sulawesi Province has a strategic role in national development. As a region that has abundant natural resources, good utilization of regional potential is a prerequisite for accelerating development in the region both from an economic and other aspect. The aim of this research is to find out whether protecting the rights of clove farmers in clove cultivation agreements is very important, because there is inequality in making agreements, where farmers who need money are easily dictated to by buyers. This research uses normative juridical methods and surveys in several villages in North Sulawesi. The social theory used in this research is Behavioral Sociology, which is a science that seeks to apply the principles of behaviorism starting from psychological theory to sociological problems. The research results show that there is no maximum protection for the rights of the farming community, especially in bond agreements, there are no special regulations such as regional regulations that regulate and provide sanctions for buyers who harm farmers, where the practice is still based on agreements. There is an urgent need for oversight by local governments of bond practices and agreements, as well as firm action against purchasers. The conclusion of this research is that regional head regulations regarding clove fishing need to be immediately established so that regional governments have a legal basis for carrying out enforcement and supervision. The novelty of this research is the need to improve the supervision system for bonded laborers by village and district governments with the existence of a bonded labor recording system which is expected to provide legal certainty in engagement agreements. Supervision also includes taking action against parties who intentionally harm farmers in unilateral agreements that harm farmers.